Cross-sectional study of risk factors associated with neonatal sepsis in a tertiary care teaching hospital - Kumar, G V; Rahman, Hareesh Fazulu; -, Vatsalakumari; Viswanathakumar, H M (Indian Journal of Child Health, 2016)
Background: Neonatal sepsis is the term that has been used to describe the systemic response to infection in newborn infants during the first 28 days of life, which can be affected by multiple risk factors. Objectives: We planned this study is carried out to determine the various risk factors associated with neonatal sepsis in the neonatal intensive care unit (NICU) of this institution. Materials and Methods: This cross-sectional study was carried out in the NICU of Sri Siddhartha Medical College and Hospital, Tumkur, Karnataka, India. All neonates up to the age of 28 days with clinical signs and symptoms, and risk factors of suspected neonatal sepsis were included in the study. Various risk factors, clinical data and investigation findings were collected and recorded on a pretested proforma. Results: Out of 60 newborn babies, 35 were male and 25 were female, and 28 cases were culture positive. Pregnancy-induced hypertension, anemia during pregnancy, and premature rupture of membranes were the most common risk factors observed in our study. The most commonly associated risk factors seen in neonates with culture positive sepsis were low birth weight (89.3%) and prematurity (89.3%) (p=0.0001) followed by respiratory distress syndrome (42.8%). Conclusion: Neonatal sepsis is quiet common, especially when associated with neonatal and maternal risk factors. Prevention of risk factors, early detection of sepsis and accurate treatment go a long way in the good outcome of neonates with sepsis.